Association between Community Nurse Engagement and Dengue Prevention Practices among Households: Evidence from a Cross-Sectional Study - Souza, Mariana; Pedro Almeida, João; Beatriz Carvalho, Ana (Global Indonesia Health Care (GOICARE), 2026)
Background: Dengue remains a major urban health burden in Brazil, with persistent transmission and widening social gradients, while evidence on whether community nurse engagement improves household prevention practices is limited. Purpose: This study aimed to estimate the association of community nurse engagement with household dengue-prevention practices among adults in Family Health Strategy micro-areas. Methods: We conducted a cross-sectional study in Ribeirão Preto, Brazil (January 1–March 30, 2025) among 543 adults (18–65 years) residing ≥6 months. Nurse engagement was a standardized composite (visit frequency/duration, content breadth, responsiveness). The outcome was a household dengue-prevention practice score (0–100), with adequate practice defined as ≥70. Modified Poisson regression with robust variance estimated adjusted prevalence ratios, adjusting for environmental, climatic, housing, infrastructure, and sociodemographic factors, with prespecified dose–response and SES interaction; missing data were imputed (m=20). Results: Among 543 participants (57.1% female; mean age 39.8 years), 48.4% achieved “adequate” practices. Higher engagement was associated with a greater probability of adequate practices (aPR 1.13, 95% CI 1.01–1.26). Compared with low engagement, high engagement showed aPR 1.21 (95% CI 1.05–1.39) with a linear trend. Effects were stronger in low-SES households (aPR per SD 1.22, 95% CI 1.06–1.41) than in high-SES households (1.05, 0.92–1.20). Results were consistent across sensitivity analyses. Conclusion: Community nurse engagement is associated with better household dengue-prevention practices. Findings support standardized nurse-led home visits paired with basic environmental fixes in similar urban settings and motivate multicentre longitudinal or pragmatic implementation studies to evaluate durability, equity, and cost-effectiveness. Relevance to clinical practice: Community nurse engagement was associated with better household dengue-prevention practices, with stronger effects in low-SES households.